2019 IEEE Symposium on Security and Privacy (SP) 2019
DOI: 10.1109/sp.2019.00072
|View full text |Cite
|
Sign up to set email alerts
|

SensorID: Sensor Calibration Fingerprinting for Smartphones

Abstract: Sensors are an essential component of many computer systems today. Mobile devices are a good example, containing a vast array of sensors from accelerometers and GPS units, to cameras and microphones. Data from these sensors are accessible to application programmers who can use this data to build context-aware applications. Good sensor accuracy is often crucial, and therefore manufacturers often use perdevice factory calibration to compensate for systematic errors introduced during manufacture. In this paper we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 19 publications
(22 reference statements)
0
26
0
Order By: Relevance
“…We have found that the gain matrix of the gyroscope in iOS devices is factory calibrated and further estimated the nominal gain for different device models based on the gyroscope outputs [2]. In particular, Table I lists the nominal gain (in mdps, millidegrees per second) of the gyroscope for all the iOS devices that we have measured.…”
Section: A Gyroscope Calibration On Ios Devicesmentioning
confidence: 99%
See 1 more Smart Citation
“…We have found that the gain matrix of the gyroscope in iOS devices is factory calibrated and further estimated the nominal gain for different device models based on the gyroscope outputs [2]. In particular, Table I lists the nominal gain (in mdps, millidegrees per second) of the gyroscope for all the iOS devices that we have measured.…”
Section: A Gyroscope Calibration On Ios Devicesmentioning
confidence: 99%
“…In our previous research we have focused mostly on iOS devices and demonstrated its effectiveness on gyroscope and magnetometer data available in iOS [2]. This paper extends our previous work: we present our latest findings on accelerometer calibration on iOS devices ( §III-E); we conduct a large-scale factory calibration behaviour analysis on popular Android device models ( §III-F); we compare the calibration fingerprint with the Fingerprintjs2 fingerprint for Google Pixel phones ( §IV-B); we analyse the calibration fingerprint for vulnerable Pixel devices and estimate entropy for each model ( §V-B).…”
Section: Introductionmentioning
confidence: 99%
“…Physical features are used in device identification. Under the analysis of the deterministic errors in the calibration process, Zhang et al [ 14 ] infer the per-device factory calibration data from the output of gyroscope, accelerometer and magnetometer. In addition to the motion sensors, the imperfection in embedded Acoustic Components can be used as the device fingerprints [ 15 ].…”
Section: Related Workmentioning
confidence: 99%
“…en, he infers a rough route and compares with the public map to get the user's motion trail. Zhang designed a fingerprinting method based on sensor calibration, which requires only the access to the sensor output [28].…”
Section: Related Workmentioning
confidence: 99%